Prevalence of Her3 in gastric cancer and its association with molecular prognostic markers: a Saudi cohort based study. Issue 1 (1st January 2019) - Ahmed, Ayesha
ABSTRACT: Her 3 is a member of epidermal growth factor receptors. Mutated, oncogenic Her3 is reported in gastric and colonic cancers with emerging evidence that Her3 can be a potential target for molecular therapies. There is a paucity of studies regarding Her3 and its prognostic implications in gastric cancer in our region. In this study, we evaluated prevalence of Her3 in gastric cancer, in a Saudi cohort of cases, along with its association with prognostic markers p53 and Ki-67. The study was conducted in Department of Pathology of King Fahd Hospital of Imam Abdulrahman Bin Faisal University, Dammam, KSA. Fifty cases of gastric carcinoma were selected from the pathology files that fulfilled the inclusion criteria. Clinico-pathological parameters, Laurens histological classification, and immunohistochemical staining for Her3, p53, and Ki-67 were done. Her 3 positive cases were also evaluated for Her-2neu co-expression. Her3 positivity was seen in 16% ( n = 8) out of a total of 50 cases. The median age of presentation was 44 years. Within Her3 positive cases, a female preponderance of 63% ( n = 5), presence of high grade tumors in 75% ( n = 6), diffuse gastric carcinoma in 63% ( n = 5), diffuse to focal p53 positivity in 63% ( n = 5), and a high to moderate Ki-67 proliferation index in 75% ( n = 6) of cases was seen. Her3 expression was independent of Her-2neu status. Her3 prevalence of 16% with a median age of 44 years at presentation was less than in other reported studies, highlighting the concept of ethnic and regional variation in tumor characteristics. Her3 association with diffuse gastric carcinoma, high grade tumors, diffuse to focal p53 positivity and high to moderate Ki-67 proliferation index points towards a more aggressive clinical behavior.